Conversation, community benefit, capacity building and social economy: A case study Łutsël K’e and the proposed national park - Bennett, Nathan (Lakehead University, 2009)
In 2001, 32 years after the Government of Canada initially proposed a national park on the East Arm of Great Slave Lake in the traditional territory of the Łutsël K’e Dene First Nation, Chief Felix Lockhart indicated to Parks Canada that the community was interested in discussing the idea. In 2006, an MOU was signed between the Government of Canada and the Łutsël K’e Dene First Nation that has lead to the withdrawal of an area of 33,525 km2 while studies, negotiations and consultations take place. The people of Łutsël K’e, Northwest Territories still have significant questions about how the creation of a national park will affect the local community and how to maximize local benefit should the park be created. This exploratory study investigated several lines of questioning related to community development and benefit, capacity building and the role of the social economy utilizing action research guided by appreciative inquiry. To gain the most insight into these issues this study used a triangulation of perspectives, employing a combination of ethnographic and formal interviews to collect data from various groups within and outside the community. The results from this research are presented in three parts. The first chapter of results focuses on perceived and desired community benefits of the creation of a national park. The second chapter discusses emergent themes related to capacity building for tourism development in the community and presents a contextual and emergent model and definition. The final chapter of results presents a discussion of the role of the social economy in supporting community development related to the creation of the park. Faculty Reviewed